A Tetravalent Cerium Complex Containing a CeO Bond1. (8th January 2014) - So, Yat‐Ming; Wang, Guo‐Cang; Li, Yang; Sung, Herman H.‐Y.; Williams, Ian D.; Lin, Zhenyang; Leung, Wa‐Hung
Abstract Whereas terminal oxo complexes of transition and actinide elements are well documented, analogous lanthanide complexes have not been reported to date. Herein, we report the synthesis and structure of a cerium(IV) oxo complex, [CeO(LOEt)2(H2O)]⋅MeC(O)NH2 (1; LOEt−=[Co(η5‐C5H5){P(O)(OEt)2}3]−), featuring a short CeO bond (1.857(3) Å). DFT calculations indicate that the hydrogen bond to cocrystallized acetamide plays a key role in stabilizing the CeO moiety of 1 in the solid state. Complex 1 exhibits oxidizing and nucleophilic reactivity.